Asociación entre síndrome de ovario poliquístico e hígado graso no alcohólico en mujeres premenopáusicas: una revisión narrativa.: Association between polycystic ovarian syndrome and nonalcoholic fatty liver disease in premenopausal women. - Arroyo Menacho, Leslie (2022)
To date there is not much research on the association between polycystic ovary syndrome and nonalcoholic fatty liver disease in premenopausal women. There is nothing consistent or conclusive about this, and it is still in controversy, however they are pathology of importance because they increase the risk of suffering from other diseases that are related to the pathogenesis they share. We set out to review the different literatures available in the following databases: PubMed, Web of Science, BVS, ScienceDirect, Scielo and ClinicalKey, Grey literature search through Medrxiv and Opengrey, manual search in main journals related to the specialty such as: Brazilian journal of Gynecology and Obstetrics, Mexican journal Gynecology and Obstetrics, Chilean journal of Obstetrics and Gynecology, Progress in Obstetrics and Gynecology journal and Cuban journal of Obstetrics and Gynecology using search terms including the following terms non alcoholic fatty liver, polycystic ovary syndrome and premenopause.